2016
DOI: 10.1515/tjb-2016-0030
|View full text |Cite
|
Sign up to set email alerts
|

Diyabetik sıçanların karaciğer ve böbrekleri üzerinde Caralluma tuberculata’nın hipoglisemik ve hipolipidemik etkisi ve güvenliği / Liquidambar orientalis Mill. reçine ekstraktlarının antioksidan, sitotoksik ve iNOS aktiviteleri

Abstract: Objective: The aim of this study is to investigate the in vitro cytotoxicity and iNOS (inducible nitric oxide synthase) inhibitory, and antioxidant activity in order to assess the traditional usage of Liquidambar orientalis Mill resin extract.Methods: Different solvent extracts of Liquidambar orientalis Mill resin were prepared. The cytotoxicity of extracts was determined using MTT (3-(4,5-dimethyl-2-thiazolyl)- 2,5-diphenyl-2H-tetrazoliumbromide) assay. HeLa (Human cervix adenocarcinoma), A-549 (Human alveola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The reduction ability of gum was 0.91 mmol TE/g in the phosphomolybdenum assay. In a literature review, although we observed several studies on the antioxidant properties of L. orientalis extracts, [20][21][22] no data were obtained for gum. At this point, the presented results could make valuable contributions to the scientific pool of the Liquidambar genus.…”
Section: Antioxidant Propertiesmentioning
confidence: 99%
“…The reduction ability of gum was 0.91 mmol TE/g in the phosphomolybdenum assay. In a literature review, although we observed several studies on the antioxidant properties of L. orientalis extracts, [20][21][22] no data were obtained for gum. At this point, the presented results could make valuable contributions to the scientific pool of the Liquidambar genus.…”
Section: Antioxidant Propertiesmentioning
confidence: 99%
“…Up to now, the chemical composition, antimicrobial, genotoxicity, mutagenicity, antioxidant potential, anti-ulcerogenic, antimutagenic and anticancer studies of styrax liquidus have been carried out. [18][19][20][21][22][23] In one of these studies, Nalbantsoy et al showed the cytotoxic, iNOS inhibition and antioxidant activity of Liquidambar orientalis Mill. Resin extracts prepared in different solvents.…”
mentioning
confidence: 99%
“…The results showed that the resin exhibited diverse cytotoxic activity against different cell types including human cervix, alveolar, breast, colon colorectal, pancreas and prostate adenocarcinoma, human glioblastomaastrocytoma and as a normal cell line human embryonic kidney cells and African green monkey kidney epithelial cells. 23 However, to the best of our knowledge, there is no study about combining this natural plant product, which has unique properties and been used among the public for many years, with any engineered polymer based scaffold. The only study on combining styrax with a biomaterial was performed by Kılınç et al and they coated surgical silk sutures with styrax liquidus and determined their anti-adhesion capacity against oral pathogenic microorganisms.…”
mentioning
confidence: 99%